GPx3 marks adipocyte lineage commitment in bone marrow stromal cells - Zhongxiang Wang; Yangyang Hu; Mao Li; Xiaojun Chen; Chengyu Zhou; Zhiyang Xu; Kai Chen; Lichuang Wu (Journal of Orthopaedic Surgery and Research)
Abstract Background Bone marrow adipose tissue (BMAT) plays an essential role in skeletal health and systemic metabolism, particularly under conditions of ageing and osteoporosis. Despite increasing recognition of BMAT as an active endocrine organ, the molecular mechanisms underlying its formation and expansion remain incompletely understood. Methods We conducted a transcriptomic re-analysis of publicly available datasets focused on the adipogenic differentiation of bone marrow stromal cells (BMSCs). Differential gene expression and pathway enrichment analyses were performed to identify key molecular changes. Validation was conducted at both the transcript and protein levels. Furthermore, re-analysis of single-cell RNA sequencing (scRNA-seq) data was employed to determine the cell type–specific expression of candidate genes within the bone marrow. Functional assays using RNA interference were carried out to investigate the role of glutathione peroxidase 3 (GPx3) in adipogenesis. Results Our analysis revealed a consistent activation of oxidative stress-related pathways during adipogenic differentiation. Among the upregulated antioxidant enzymes, GPx3 was selectively increased during adipogenic—but not osteogenic—differentiation. This pattern was validated at both mRNA and protein levels in vitro. scRNA-seq analysis showed that GPx3 expression is predominantly localized in BMSCs and adipocytes, with reduced expression observed in aged mice, corresponding to elevated levels of adipocyte-related genes. In vitro functional experiments demonstrated that GPx3 knockdown significantly promoted adipogenic differentiation of BMSCs. Conclusion These findings indicate that GPx3 is closely associated with adipocyte lineage commitment within the bone marrow microenvironment and may serve as a key modulator of BMSC fate. This study underscores the potential role of antioxidant enzymes such as GPx3 in the regulation of age-related bone-fat imbalance and highlights their relevance in metabolic bone disorders.